Welfare implications of Calvo vs. Rotemberg pricing assumptions - Giovanni Lombardo; David Vestin (European Central Bank (ECB), 2007)
This paper compares the welfare implications of two widely used pricing assumptions in the New-Keynesian literature: Calvo-pricing vs. Rotemberg-pricing. We show that despite the strong similarities between the two assumptions to a first order of approximation, in general they might entail different welfare costs at higher order of approximation. In the special case of non-distorted steady state, the two pricing assumptions imply identical welfare losses to a second order of approximation.
Keywords: E3; E5; 330; Calvo price adjustment; inflation; Rotemberg price adjustment; second-order approximation; Welfare; Marktmechanismus; Preismanagement; Neoklassische Synthese; Theorie